Racial and geographic disparities in the patterns of care and costs at the end of life for patients with lung cancer in 2007–2010 after the 2006 introduction of bevacizumab. Issue 3 (December 2015) - Du, Xianglin L.; Parikh, Rohan C.; Lairson, David R.
Highlights: Cancer care varied by areas in last 6 months of life among lung cancer decedents. There were substantial racial disparities in cancer care in last 6 months of life. Disparities were apparent in types of care and costs in lung cancer decedents. Clinical guideline may be needed to minimize racial/geographic disparities. Abstract: Objectives: To examine racial/ethnic and geographical disparities in cancer care and costs during the last 6 months of life for lung cancer decedents after the Food and Drug Administration's approval of expensive bevacizumab in October 2006. Methods: We identified 37, 393 cases from the Surveillance, Epidemiology and End Results (SEER) cancer registries and Medicare linked databases who were diagnosed with non-small cell lung cancer of all stages in 1991–2009 and died between July 2007 and December 2010. Results: Overall, the proportion of patients receiving chemotherapy/targeted therapy (31.0%), bevacizumab (4.6%), growth factors (16.0%), surgery (2.8%), and hospice care (60.9) in the last 6 months of life was higher in whites than in other ethnic populations. Hospitalization rate was higher in blacks (83.2%) than in whites (76.0%) and others (78.0%). Those from metro areas had slightly higher percentages of receiving chemotherapy/targeted therapy, bevacizumab, growth factors, and hospice care, but had a higher hospitalization rate and lower emergency care visit. Mean total health care cost was $42, 749 for the last 6 months of life in patients with lung cancer. Adjusted mean health care cost in the last 6 months of life was significantly higher in blacks or other ethnic population as compared to whites. Conclusion: There were substantial racial/ethnic and geographic disparities in the types of cancer care and costs in the last 6 months of life among lung cancer decedents, regardless of the length of survival times and hospice care status. A clinical guideline may help the appropriate use of costly treatment modalities and minimize racial/geographic disparities.